STOCHASTIC METHODS OF STEEL CONSTRUCTIONS’ CALCULATION OF THE SILO CAPACITIES AT THE SEISMIC STABILITY - Makhinko, Nataliia (Proceedings of National Aviation University (archive), 2019)
The paper deals with the technique of assessment of the reliability function of the construction of vertical cylindrical silos under the seismic influence. The developed approach is based on the theory of the static seismic stability, which was worked out by V.V. Bolotin. The random character of geotectonic excitation and stochastic features of the material is considered. The introduced technique could be used both for direct stochastic calculations of constructions of the silo capacity and for the general normalization of seismic influences on buildings and constructions. The assessment of conditional probability of construction’s failure is received in two variants: accordingly to the model of absolute maximums and on the basis of the exponential model, which was based on the Poisson classification. Mentioned convenient practical formulas to determine full reliability functions represent analytical complex expression, which combine different parameters: the proper frequency of the construction, the duration of intense phase of the earthquake, the parameter of repeatability of the earthquake, stochastic characteristics of the charging effect of the construction, useful life of the construction and others. The finiteness of the expounded material is the use of the described approach only for constructions, which works linearly. But, if the non-linearity of the construction is rather small we could use statistic linearization method, which is widely used in general theory of building construction’s reliability and could be successfully used in this case.